Epidemiology of cryptosporidiosis in HIV- infected individuals - a global perspective - Iqbal, A.; Lim, A.I.; Al Mahdy, M.; Dixon, B.; Surin, Johari (OMICS International, 2012)
Cryptosporidiosis, resulting from infection with the protozoan parasite Cryptosporidium, is a significant opportunistic disease among HIV-infected individuals. With multiple routes of infection due to the recalcitrant nature of its infectious stage in the environment, the formulation of effective and practical control strategies for cryptosporidiosis must be based on a firm understanding of its epidemiology. Prevalence data and molecular characterization of Cryptosporidium in HIV-infected individuals is currently available from numerous countries in Africa, Asia, Europe, North America and South America, and it is clear that significant differences exist between developing and developed regions. This review highlights the current global status of Cryptosporidium infections among HIV-infected individuals, and puts forth a contextual framework for the development of integrated surveillance and control programs for cryptosporidiosis in immune compromised patients. Given that there are few specific chemotherapeutic agents available for cryptosporidiosis, and therapy is largely based on improving the patient’s immune status, the focus should be on patient compliance and non-compliance obstacles to the effective delivery of health care, as well as educating HIV-infected individuals in the prevention of infection. This would require close collaborations amongst public health professionals, governmental officials, researchers, epidemiologists and clinicians, as well as the targeted HIV-infected individuals themselves.